1971
DOI: 10.1097/00132586-197112000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Fulminating Hyperpyrexia During Anaesthesia in a Member of a Myopathic Family

Abstract: We would like to thank Mr. W. D. Park, consultant surgeon, and Mr. Bernard Fairburn, consultant neurosurgeon, for permission to publish details of cases under their care. We are indebted to Mr. Sheppard for the photographs, and to the neurological department of the London Hospital for their assistance in the diagnosis of Barnes's myopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1971
1971
1976
1976

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Some reports comment upon muscle hypertrophy in susceptible subjects (Steers et al, 1970;King et al, 1972;Harriman et al, 1973). The pathological changes observed in muscle biopsies are variable and non-specific (Harriman et al, 1973;Isaacs et al, 1973;Ellis et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports comment upon muscle hypertrophy in susceptible subjects (Steers et al, 1970;King et al, 1972;Harriman et al, 1973). The pathological changes observed in muscle biopsies are variable and non-specific (Harriman et al, 1973;Isaacs et al, 1973;Ellis et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…TM In addition, there are statistical 1~176176 and genetic analyses. 44,46,61,81,1~176 There are a number of descriptions of malignant h v]3er-thermia in pigs ~~ in which the manifestations are similar to those in man. Several biochemical and microscopic 12~ studies exploring the cause of porcine malignant hyperthermia have been published, but their results and conclusions are not uniform.…”
Section: Introductionmentioning
confidence: 99%
“…10,17,26,74,81,99,101,108,109,141,143,145,146,150,158,187,188,189 This is not to say that the defects must be confined to skeletal muscle, nor does this necessarily mean that a defect in muscle is the primary lesion. 99,14~…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their confirmation of the value of CPK in carrier detection, they found clinical evidence of myopathy. Steers et al (1970) found evidence of a myopathy in their susceptible family similar to that described by Barnes (1932). King, Denborough, and Zapf (1972) have suggested that susceptible individuals may show one of a number of specific myopathies consisting of a group with a dominantly inherited myopathy, a group who have myotonia congenita, and a third group with physical abnormalities and a progressive congenital myopathy.…”
mentioning
confidence: 57%